2017
DOI: 10.1111/jfr3.12289
|View full text |Cite
|
Sign up to set email alerts
|

Land use influence on flood routing and retention from the viewpoint of hydromechanics

Abstract: Implementing new concepts and measures for flood risk management may be restricted by hydromechanical processes. These processes govern the movement of water masses within rivers and their floodplains. Different hydraulic processes are still not fully understood or cannot be described satisfactorily by hydro‐numerical models due to uncertainty in input data. The choosing of the correct surface roughness has a huge influence on the results of hydro‐numerical calculation of historical and design flood events and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
1
14
0
Order By: Relevance
“…The second intervention was in-channel woody debris, which aims to introduce storage through upstream ponding and slow channel flows sufficiently to have an alleviating impact in smaller events [29]. Several physical studies have reinforced this hypothesis [30,31].…”
Section: (B) Interventionsmentioning
confidence: 99%
“…The second intervention was in-channel woody debris, which aims to introduce storage through upstream ponding and slow channel flows sufficiently to have an alleviating impact in smaller events [29]. Several physical studies have reinforced this hypothesis [30,31].…”
Section: (B) Interventionsmentioning
confidence: 99%
“…In order to understand flood routing and protection, one must know that the flow in every river or channel is subjected to a small peak reduction, which is caused by the different hydraulic gradients of the coming and leaving flood wave (Bornschein and Pohl 2017). This brings a higher propagation celerity of the flood wavefront and a slower velocity on the reverse side of the wave.…”
Section: Hydraulic Aspects Of Wetland Retentionmentioning
confidence: 99%
“…According to long-term disaster records, some studies have revealed an increase in the losses due to extreme weather events (Mechler and Kundzewicz, 2010;Peduzzi et al, 2009;Swiss Re, 2016;UNISDR, 2009). The long-term trends in these losses are attributed to the increasing exposure of people and economic assets in at-risk areas due to population and economic growth (Bouwer, 2011;Changnon et al, 2000;Miller et al, 2008;Pielke Jr. et al, 2005) rather than to climatic drivers (Choi and Fischer, 2003;Crompton and McAneney, 2008;Neumayer and Barthel, 2011). This can be extrapolated to inundations (Barredo, 2009;Hilker et al, 2009;Pielke Jr. and Downton, 2000) and hence to the dam risk framework.…”
Section: Direct Consequencesmentioning
confidence: 99%